Phytochemical Screening, Antioxidant Capacity Measurement, and Mineral Content Determination of Thymus vulgaris L. Extracts - Elsherif, Khaled Muftah; Ewlad-Ahmed, Abdunaser Mabrok Mabrok; Alhlbad, Ebtesam Abdallah Ahmed; Iqneebir, Abdulrhman Mohammed (Walisongo Journal of Chemistry, 2023)
The aim of this study was to evaluate the chemical composition and antioxidant activity of Thymus vulgaris L. extracts. T. vulgaris L. is a medicinal plant that has various bioactive compounds. Four different solvents (ethanol, water, ethyl acetate, and chloroform) were used to extract these compounds from the plant. The phytochemical screening of the extracts showed that the ethanolic extract had the highest diversity of compounds, including coumarins, flavonoids, alkaloids, tannins, phenols, carbohydrates, and proteins. The total phenolic and total antioxidant contents of the ethanolic extract were measured by the Folin–Ciocalteu and phosphomolybdenum methods, respectively. The ethanolic extract had a high phenolic content of 77.7 mg gallic acid equivalent/g dry weight, which indicates its potential antioxidant capacity. The mineral content of T. vulgaris L. was also assessed by flame photometry and atomic absorption spectrophotometry after dry digestion. The plant contained five macroelements (K, Na, Ca, Mg, P) and three microelements (Fe, Cu, Zn) in different concentrations. The highest concentration was found for potassium (15259 mg/kg), followed by calcium (5118 mg/kg) and sodium (4793 mg/kg). The lowest concentration was found for phosphorus (1400 mg/kg), which was still higher than the microelements. Among the microelements, zinc had the highest concentration (24.82 mg/kg), followed by iron (17.44 mg/kg) and copper (14.98 mg/kg). The results of this study provide useful information for the users, collectors and practitioners of medicinal plants from polluted areas, as they can evaluate the quality and safety of T. vulgaris L. for human consumption.